An investigation into the health-promoting behaviors and their associated factors in 18-29 year-old youth of Khorramabad city in 2020 - Khatereh Anbari; Pardis Ghanadi; Amir Hossein Bagheri (Journal of Biological Research, 2022)
Health-promoting behaviors and healthy lifestyle are the main strategies to preserve people's health. Considering the importance of the youth's health in promoting the society's health, the present study was conducted to investigate the health-promoting behaviors and their associated factors in 18-29year-old youth of Khorramabad city in 2020. In this cross-sectional study, 358 individuals aged 18 to 29 years living in Khorramabad city in the first half of 2020 were included. This research sample was selected using a stratified multistage random sampling method. First, Khorramabad city was divided into three regions: north, central, and south regions based on the urban map. Then, two therapeutic health centers, two recreation centers, two educational centers, two business centers, and two religious cultural centers were randomly selected from each region. After that, the eligible samples were selected to enter the study by applying the convenience sampling method from each of these centers proportional to the calculated sample size. The sample size was estimated to be 358 people. The data was analyzed using SPSS software version 19.0. Descriptive statistical methods, such as mean, standard deviation and ratios, and frequency percentages were used to describe the terms. In addition, independent-t test, one-way analysis of variance (ANOVA), and linear regression analysis were used to analyze data. The mean age of the study participants was 24.6 ± 2.6 years. Of the total participants in the study, 217 (60.6%) were male and the rest were female. The total mean score of health-promoting behaviors in participants of the study was 122.6±16.13 (achievable range: 52-208). Overall, the status of health-promoting behaviors was undesirable in 12% of participants, moderate in 87.4%, and desirable in 0.6%. In univariate analysis, the difference in the total score of health-promoting behaviors was statistically significant between the subjects by gender (PV = 0.002), marital status (0.049), education level (0.001), occupation (<0.001) and history of regular smoking (<0.001).In linear regression analysis, gender, marital status, education level, and occupation were the most important predictors of health-promoting behaviors in the participants of this study. Considering the pivotal role of youth in society, proper planning seems necessary to improve their performance in the area of health promotion.